Intestinal bacterial overgrowth in the early stage of severe acute pancreatitis is associated with acute respiratory distress syndrome - Liang, Xue-Ying (World J Gastroenterol, 2021)
BACKGROUND: In the early stage of acute pancreatitis (AP), a large number of cytokines induced by local pancreatic inflammation seriously damage the intestinal barrier function, and intestinal bacteria and endotoxins enter the blood, causing inflammatory storm, resulting in multiple organ failure, infectious complications, and other disorders, eventually leading to death. Intestinal failure occurs early in the course of AP, accelerating its development. As an alternative method to detect small intestinal bacterial overgrowth, the hydrogen breath test is safe, noninvasive, and convenient, reflecting the number of intestinal bacteria in AP indirectly. This study aimed to investigate the changes in intestinal bacteria measured using the hydrogen breath test in the early stage of AP to clarify the relationship between intestinal bacteria and acute lung injury (ALI)/acute respiratory distress syndrome (ARDS). Early clinical intervention and maintenance of intestinal barrier function would be highly beneficial in controlling the development of severe acute pancreatitis (SAP). AIM: To analyze the relationship between intestinal bacteria change and ALI/ARDS in the early stage of SAP. METHODS: A total of 149 patients with AP admitted to the intensive care unit of the Digestive Department, Xuanwu Hospital, Capital Medical University from 2016 to 2019 were finally enrolled, following compliance with the inclusion and exclusion criteria. The results of the hydrogen breath test within 1 wk of admission were collected, and the hydrogen production rates at admission, 72 h, and 96 h were calculated. The higher the hydrogen production rates the more bacteria in the small intestine. First, according to the improved Marshall scoring system in the 2012 Atlanta Consensus on New Standards for Classification of Acute Pancreatitis, 66 patients with a PaO(2)/FiO(2) score ≤ 1 were included in the mild AP (MAP) group, 18 patients with a PaO(2)/FiO(2) score ≥ 2 and duration < 48 h were included in the moderately SAP (MSAP) group, and 65 patients with a PaO(2)/FiO(2) score ≥ 2 and duration > 48 h were included in the SAP group, to analyze the correlation between intestinal bacterial overgrowth and organ failure in AP. Second, ALI (PaO(2)/FiO(2 )= 2) and ARDS (PaO(2)/FiO(2 )> 2) were defined according to the simplified diagnostic criteria proposed by the 1994 European Union Conference. The MSAP group was divided into two groups according to the PaO(2)/FiO(2) score: 15 patients with PaO(2)/FiO(2) score = 2 were included in group A, and three patients with score > 2 were included in group B. Similarly, the SAP group was divided into two groups: 28 patients with score = 2 were included in group C, and 37 patients with score > 2 were included in group D, to analyze the correlation between intestinal bacterial overgrowth and ALI/ARDS in AP. RESULTS: A total of 149 patients were included: 66 patients in the MAP group, of whom 53 patients were male (80.3%) and 13 patients were female (19.7%); 18 patients in the MSAP group, of whom 13 patients were male (72.2%) and 5 patients were female (27.8%); 65 patients in the SAP group, of whom 48 patients were male (73.8%) and 17 patients were female (26.2%). There was no significant difference in interleukin-6 and procalcitonin among the MAP, MSAP, and SAP groups (P = 0.445 and P = 0.399, respectively). There was no significant difference in the growth of intestinal bacteria among the MAP, MSAP, and SAP groups (P = 0.649). There was no significant difference in the growth of small intestinal bacteria between group A and group B (P = 0.353). There was a significant difference in the growth of small intestinal bacteria between group C and group D (P = 0.038). CONCLUSION: Intestinal bacterial overgrowth in the early stage of SAP is correlated with ARDS.